The Morgans private international bankers, 1854-1913 - Carosso, Vincent P.; Carosso, Rose C. (Harvard studies in business history, 1987)
The House of Morgan personified economic power in the late 19th/early 20th centuries. Carosso constructs an in-depth account of the evolution, operations, and management of the Morgan banks at London, New York, Philadelphia, and Paris, from the time Junius Spencer Morgan left Boston for London to the death of his son, John Pierpont Morgan